Single-cell sequencing revealed the necessity of macrophages in brain microenvironment remodeling by breast cancer metastasis - Maotang Liu; CenZhu Wang; Qin Hu; XueChao Wu; Qing Wang; Jing Wang; Kun Xu; XiaoJie Lu; Wei Tian (Translational Oncology)
Breast cancer is one of the most common cancers worldwide, 30–50 % of patients with advanced breast cancer develop brain metastasis, causing severe damage to their life quality. Due to the existence of the blood-brain barrier (BBB), brain lesions were recognized to be a unique microenvironment with limited infiltration of circulating immune cells and drugs. However, emerging studies reported the immunology of the brain tumor microenvironment (TME) and indicated the potential of immunotherapy against brain metastases. Therefore, it is of great value to comprehensively investigate the TME and identify the pro-tumoral mechanisms facilitating brain metastases and the crucial molecules involved in this process. In this research, we re-analyzed public data on three brain surgical specimens of breast cancer metastases and identified the immunosuppressive roles of macrophages in the metastatic TME. Then, we conducted the first single-cell RNA sequencing on a murine model of breast cancer brain metastasis. In the brain TME, immune cells showed prominent heterogeneity, especially the mononuclear phagocyte system (MPS). We identified the alteration of macrophage subclusters in the central nerve system (CNS) after breast cancer invasion and found that metastatic cancer cells re-shaped the TME cellular interactions for immune evasion and nutrition supply. Finally, this research could serve as a reference for further analysis of new therapies against brain metastatic lesions.